G46 A clinical prediction tool (cpt) to identify maltreatment in children with burns and scalds. (27th April 2015) - Kemp, AM; Hollen, L; Rea, D; Pawlik, MC; Nuttall, D; Emond, A; Maguire, S
Abstract : Aims: An estimated 10% of childhood burns arise from neglect or physical abuse. The challenge for emergency department (ED) staff with limited child protection training and a high staff turn over is to recognise these children. The aim of this study is to design an evidence-based CPT to assess the risk of maltreatment in a child who presents to ED with a burn or scald. Methods: Derivation: An evidence-based proforma Burns and Scalds Assessment Tool (BaSAT) was developed from a systematic review of the characteristics of burns or scalds due to maltreatment. Standardised data were collected on 1327 children <16 years presenting to EDs in the UK and Ireland (2008–10). A CPT for risk of maltreatment was derived from a logistic regression model of several influential factors for the referral of 112/1327 cases to Social Care, namely; age < 5 years, known to social services, inappropriate injury explanation, full thickness burn, atypical body location, bilateral symmetry and supervision concerns. Based on the predicted probabilities from the logistic regression, the CPT was adapted into a simple scoring system to grade cases as 'concern'/'no concern' for child maltreatment. Validation: data on children with burns attending four UK EDs were collected prospectively (2013–14) on a revised BaSAT, and the CPT prediction validated against child protection referrals to social services. Results: The validation: Of 789 children (median age 30 months) with burns, 7% (54) were referred to social services. The CPT classified 19% (74/389) scalds, and 26% (104/400) burns as 'concern'. For scalds the sensitivity for identification of children referred to social care was 83% (95% CI 59–96%) and specificity was 84% (95% CI 80–88%) for scalds; positive likelihood ratio (LR+) 5.2 for non scalds the sensitivity was 81% (95% CI 64–92%) and specificity of 79% (95% CI 74–83%) for non-scalds; LR+ 3.9. Conclusions: The CPT shows promise as an aid to clinical decision making in the ED setting. In conjunction with the BaSAT it provides standardised clinical assessment and documentation of children with burns/scalds and a prediction of the likelihood of maltreatment. Its applicability and accuracy will now be tested in an implementation evaluation.